gwp 2014
DOI: 10.24149/gwp218
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Deflation from a Fiscal Perspective

Abstract: Negative correlations between inflation and demographic aging were observed across developed nations recently. To understand the phenomenon from a politico-economic perspective, we embed the fiscal theory of the price level into an overlapping-generations model. In the model, successive short-lived governments choose income tax rates and bond issues considering the political influence of existing generations and the policy response of future governments. The model sheds new light on the traditional debate abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In totality, aging population has become a major financial burden on for regional governments [8][9][10][11]. In another research study, it was reported that an aging society would lead to a decrease in household saving rate [12][13][14]. Ando and Modigliani (1954) [15] proposed the Life Cycle Theory of Consumption: retirees can sell off their assets to provide for food, housing, and recreation in retirement homes; this would contribute to a dissaving status.…”
Section: Plos Onementioning
confidence: 99%
“…In totality, aging population has become a major financial burden on for regional governments [8][9][10][11]. In another research study, it was reported that an aging society would lead to a decrease in household saving rate [12][13][14]. Ando and Modigliani (1954) [15] proposed the Life Cycle Theory of Consumption: retirees can sell off their assets to provide for food, housing, and recreation in retirement homes; this would contribute to a dissaving status.…”
Section: Plos Onementioning
confidence: 99%